School Board Presidents Describe Critical Incidents with Superintendents - Marilyn L. Grady; Miles T. Bryant (Journal of Research in Rural Education, 1991)
Thepurpose of this study was to identify what school boardpresidentsperceived to be critical incidents with their superintendents. Eighty-seven percent (87%) of school board presidents in Nebraska responded. Of these 239 superintendents, 68 (28%) experienceda critical incidentand 60 (88%) agreed to discuss the incidents. Incidents weregrouped into 11 categories: Communication/human relations, staffing, ethics, competence, personal issues, finance, athletics, credentials, policy, New Age Church, and board members. The findings of this study have implications for the field of educationaladministration, preparationprograms, state and local professional associations, and superintendent and school board memberroles.